Magnetic Resonance Morphometry of Normal Cerebral Aqueduct in South Indian Population - Veeramani Raveendranath; Prafulla Kumar Dash; Thangaraj Kavitha; Krishnan Nagarajan (Indian Journal of Neurosurgery, 2022)
Introduction Cerebral aqueduct (of Sylvius) connects the third and fourth ventricles of the brain, and the shape of the aqueduct varies. The aim of the study is to assess the morphometry of the cerebral aqueduct in normal south Indian adult population and to look for pattern by shape, if any. Materials and Methods One hundred and fifty normal brain MR images (75 males and 75 females) using 3D heavily T2-weighted sequence were analyzed for various normal parameters of cerebral aqueduct. Mean and standard deviation were calculated. Based on the shape of the aqueduct, an attempt was made to classify them. Unpaired t-test was used to assess any significant difference between age groups and gender. The intraclass coefficient correlation was used to analyze the interobserver variability. Results The mean value of the length of the cranial and caudal part of aqueduct in males were 0.69 cm and 0.86 cm and in females 0.65 cm and 0.80 cm, respectively. The length was more in males, and it was statistically significant (p = 0.006 and 0.02). There are four types of cerebral aqueduct based on shape. Conclusion MRI is considered as the investigation of choice for preoperative planning of brain operative procedures. The MR morphometric evaluation of cerebral aqueduct provides precise knowledge about the anatomy and may be of help in the diagnosis and treatment by endoscopic neurosurgery.